SISTEM TES BERBASIS KOMPUTER UNTUK SELEKSI MITRA BADAN PUSAT STATISTIK - Adhi Candra Maulana; Nori Wilantika (Seminar Nasional Official Statistics, 2020)
With a mission to provide high quality statistical data, the data provided by the Statistics Indonesia (Central Bureau of Statistics) must have a small total survey error. The total survey error includes both sampling error and nonsampling error, with nonsampling error playing a bigger role. In surveys or censuses carried out by BPS, the non-ampling error is strongly influenced by the quality of field officers recruited by BPS or commonly referred as “mitra statistik”. High quality “mitra statistik” are recruited through an assessment test. The current assessment test process is still using the Paper and Pencil Test (PPT) method. This method has several problems, especially the safety of the questions and the transparency of the participants' scores. This study aims to develop a computer-based test system to solve problems in the current exam system. The system development method is the modified waterfall method. The result of this research is a computer-based test system called SICATMiS which was developed from OSS TCExam. The system has 3 actors and 5 main menus that can run online or offline. SICATMiS was evaluated using scenario test, user acceptance test, and system usability scale. The scenario test results show that of the 47 scenarios performed, all features were executed perfectly. Of the 14 statements in the user acceptance test, 68% of respondents strongly agree that SICATMiS has met user needs. The SUS evaluation also showed that SICATMiS was very well received and ready to use.